Extracellular Vesicles Regulated by Viruses and Antiviral Strategies - Yang, Li; Li, Jing; Li, Shen; Dang, Wei; Xin, Shuyu; Long, Sijing; Zhang, Wentao; Cao, Pengfei; Lu, Jianhong (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs), consisting of exosomes, micro-vesicles and other vesicles, mainly originate from multi-vesicular body (MVB) pathway or plasma membrane. EVs are increasingly recognized as a tool to mediate the intercellular communication and are closely related to human health. Viral infection is associated with various diseases, including respiratory diseases, neurological diseases, and cancers. Accumulating studies have shown that viruses could modulate their infection ability and pathogenicity through regulating component and function of EVs. Non-coding RNA (ncRNA) molecules are often targets of viruses and also serve as the main functional cargo of virus-related EVs, which have important role in epigenetic regulation of target cells. In this review, we summarize the research progress of EVs under the regulation of viruses, highlighting the content alteration and function of virus-regulated EVs, emphasizing their isolation methods in the context of virus infection, and potential antiviral strategies based on their use. This review would promote the understanding of the viral pathogenesis and the development of antiviral research.